The biochemistry of the basal ganglia and Parkinson's disease. Issue 626 (December 1977) - Curzon, G.
Abstract : The metabolic pathways for five transmitters in the basal ganglia are briefly described; the results of determinations of their concentrations, of their rate-limiting enzymes and of their degradation products are summarized. The changes found in Parkinson's disease are described. While dopamine synthesis in the basal ganglia is defective in this condition, abnormalities of other transmitters occur, and their possible significance is discussed.